A retirement mobilities approach to transnational ageing - Nedelcu, M.; Tomás, L.; Ravazzini, L.; Azevedo, L. (Mobilities, 2024)
Transnational ageing processes are usually studied by focusing on thevarious cross-border practices and mobilities of different categories ofageing migrants. This paper introduces aretirement mobilitiesapproachas an analytical framework that draws on both transnational studies andthe new mobilities paradigm to widen the theoretical and empiricaldebates. It argues that both migrant and non-migrant populations, aswell as human and non-human cross-border circulations, have to betaken into account when studying transnational ageing. Based on amixed-methods study combining original data from a quantitative sur-vey conducted in Switzerland with residents 55þand semi-structuredinterviews held in Spain and Switzerland with older adults receiving aSwiss pension, we demonstrate the heuristic value of this approach.Indeed, empirical findings indicate that older adults with and without amigration background represent an internationally mobile populationwith similar mobility aspirations and transnational lifestyles. However,the motivations driving these two groups’transnational mobility differsignificantly. Moreover, transnational circulations of financial resources,and in particular retirement pensions, are interlinked with mobility inold age. To conclude, aretirement mobilitiesapproach sets a newresearch agenda, inviting scholars to examine transnational ageingbeyond the ageing-migration nexus.